Symbolic Meaning of Malay Culture in North Sumatra - Harianto II; Zulfitri; Teguh Satria Amin (PT Inovasi Pratama Internasional, 2023)
The purpose of this study is to describe a desire and also the purpose of using identity and symbols from Malay ethnicity and culture in the North Sumatra region. The results of research in the field will be analyzed using theory based on social action with research methods that use qualitative as well as quantitative case studies in North Sumatra. Data collection using detailed interview methods and also observations from respondents in North Sumatra. The data analysis used in this research method reveals various symbols of Malay culture in North Sumatra which have messages to convey to the wider community regarding traditions, culture and local wisdom in North Sumatra. Symbols are media that can be used to reinforce a status that has a relationship with power and also the human and natural resources in North Sumatra. The symbol of Malay identity in North Sumatra in the post-reformation era became one of the actions taken by Malay people as a form of existence for the Malay community to show their concern for local cultures in North Sumatra. This action is one of the motives of the Malay ethnicity in North Sumatra to change the potential for relations between ethnic groups in North Sumatra in order to maintain local wisdom and also hold the strategic side in North Sumatra. So that it can increase the value of Malay culture in North Sumatra.